Gross Anatomical Studies on the Tibia and Fibula of Rhesus Monkey (Macaca mulatta) - Kamal Sarma, (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the tibia and fibula bones obtained from carcass of one adult rhesusmonkey. The tibia bone was a long, thick prismatic bone. Shaft was 3 sided throughout its proximal half. Distalend was cylindrical. Lateral surface presented a shallow sulcus muscularis. Caudal surface had a single indistinctrd popliteal line. Medial surface was slightly convex up to distal 3 of its length. The nutrient foramen was located inrd th upper 3 of tibia close to the lateral border. Anterior border was prominent in its upper 4 and constituted the tibialcrest. The distal extremity was quadrilateral in outline. It presented two deep antero-posterior grooves separatedby a ridge. Fibula was laterally compressed bone lateral to the tibia. It consisted of a proximal head, shaft anddistally lateral malleolus. Tibial index was recorded as 0.05. Tibial platymeric index was found to be 0.56. Tibialmid-shaft index represented the ratio of tibial proximal condyles to its shaft. It was 0.28. Distal tibial index wasrecorded as 0.85.